Interaction between mesenchymal stromal cells and tuberculous mycobacteria in vitro - S. N. Belogorodtsev; A. P. Lykov; E. K. Nemkova; Ya. Sh. Schwartz (Туберкулез и болезни лёгких)
The objective: in an in vitro experiment, we compared phagocytic parameters of mesenchymal stromal cells (MSCs) and macrophages to tuberculous mycobacteria, assessed the ability of MSCs and macrophages to lyse mycobacteria or maintain their intracellular growth, their effect on formation of phenotypic drug resistance of mycobacteria, as well as the effect of tuberculous mycobacteria on the type of MSCs cell death.Subjects and Methods. Balb/c male mice, aged 6 to 8 weeks, were used in the experiment. Bone marrow MSCs were obtained from femurs and tibias by further cultivation, peritoneal macrophages were elicited with 4% alpha-glucan. The intracellular content of mycobacteria was counted using a confocal microscope with x 400 magnification. Susceptibility of mycobacteria to isoniazid and development of phenotypic drug resistance after culturing MSCs and macrophages with MTB on Lowenstein–Jensen medium was assessed by counting CFU. In 5 days after the infection, the number of apoptotic and necrotic MSCs and macrophages was determined by a flow cytometer.Results. On Day 1, the total number of phagocytosed MTB, as well as the number of phagocytic-active macrophages, exceeds the corresponding figures for MSCs more than twice. MSCs phagocytize tuberculous mycobacteria in a smaller amount, but MTB reproduces in them more actively: the number of CFU after 7 days of cell cultivation with MTB exceeded the corresponding parameter by almost 50 times after 24 hours of cultivation. In cultures of infected MSCs cultivated for 7 days, regardless of the presence of isoniazid, there was a rapid growth of tuberculous mycobacteria. On Day 5 after infection of macrophage culture with tuberculous mycobacteria, the number of necrotic cells was 2.7 times greater than that of uninfected necrotic macrophages, but the number of apototic cells in these groups differed slightly. In the culture of MSCs, there were 8.5 times more infected nectrotic cells versus uninfected necrotic MSCs, and the number of necrotic MSCs was 4.5 times higher than the number of MSCs with apoptosis, while in the culture of infected macrophages, the number of necrotic cells was the same as number of apoptotic cells. Unlike macrophages, treatment of MSCs with isoniazid did not inhibit the intracellular proliferation of MTB.Conclusion. MSCs have the ability to phagocytose mycobacteria, but they do it less actively than macrophages and, unlike macrophages, they are not able to restrain the reproduction of tuberculous mycobacteria. Mycobacteria have phenotypic drug resistance in MSCs. In MSCs, when infected with tuberculous mycobacteria, there is a pronounced shift towards necrosis in the type of cell death, which can lead to dissemination of MTB and development of local destructive changes.